2000
DOI: 10.4049/jimmunol.164.7.3862
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Functional IL-8 Receptors by IL-4 and IL-13 in Human Monocytes

Abstract: IL-8 and related Glu-Leu-Arg (ELR+) CXC chemokines are potent chemoattractants for neutrophils but not for monocytes. IL-13 and IL-4 strongly increased CXCR1 and CXCR2 chemokine receptor expression in human monocytes, macrophages, and dendritic cells. The effect was receptor- and cell type-selective, in that CCRs were not increased and no augmentation was seen in neutrophils. The effect was rapid, starting at 4 h, and concentration dependent (EC50 = 6.2 and 8.3 ng/ml for CXCR1 and CXCR2, respectively) and caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(78 citation statements)
references
References 73 publications
5
73
0
Order By: Relevance
“…A previous study has suggested that CXCR1 and CXCR2 were nonfunctional in DCs derived in culture with GM-CSF and IL-13 in spite of detectable expression of the receptors. 23 Reasons for the discrepancy between these data and our own might involve differentiation conditions of DCs in culture.…”
Section: Dcs Are Responsive To Il-8mentioning
confidence: 50%
See 1 more Smart Citation
“…A previous study has suggested that CXCR1 and CXCR2 were nonfunctional in DCs derived in culture with GM-CSF and IL-13 in spite of detectable expression of the receptors. 23 Reasons for the discrepancy between these data and our own might involve differentiation conditions of DCs in culture.…”
Section: Dcs Are Responsive To Il-8mentioning
confidence: 50%
“…Several reports had demonstrated that IL-8 was secreted by malignant cells in human digestive carcinomas, 5,[35][36][37] while genetic evidence in mice indicated a role for IL-8 in angiogenesis and metastasis. We thought that the chemotactic activity of IL-8, previously characterized on polymorphonuclear leukocytes (PMNs), 6 monocytes 23 and endothelial cells, 8 could be involved in intratumoral retention of DCs, provided that DCs would respond to IL-8.…”
Section: Discussionmentioning
confidence: 99%
“…IL-4 has been shown to increase the expression of chemokine receptors CXCR1 and CXCR2, which are counter-receptors to IL-8 and Gro-␣, thus making monocyte/macrophages responsive to IL-8 (40). In addition we have recently demonstrated that blockade of Gro-␣ receptor on the macrophage surface reduces their ability to localize to inflamed glomeruli with NTN within 24 h of the onset of disease (4).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, CXCR2 expression is highly regulated by cytokines such as IL-4, IL-10, and IL-13 and by other factors that may regulate vascular inflammation in vivo. [35][36][37][38] In the intermediate atherosclerosis stage, macrophages in the lesions of the CXCR2 Ϫ/Ϫ BMT mice were located more superficially on the lumenal side of the intima rather than dispersed throughout the intima as in the CXCR2 ϩ/ϩ BMT mice. Moreover, in the advanced stages of atherosclerosis, the lesions of the CXCR2 Ϫ/Ϫ BMT mice demonstrated little progression beyond the intermediate stage with a relatively marked decline in lesion macrophage staining.…”
Section: Discussionmentioning
confidence: 99%